(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health issue in Indonesia, particularly among high school students. Limited knowledge regarding mosquito vector characteristics, breeding habitats, and larvae monitoring hampers community-based prevention efforts. This community service activity aimed to strengthen the role of high school students as agents of change in dengue prevention through the dissemination of the Jumantik guidebook. The method employed was Participatory Action Research (PAR) involving 55 high school students who are members of the Youth Red Cross (PMR) from various schools in Tasikmalaya City. The activity was conducted online via Zoom, followed by a questionnaire to evaluate participants’ knowledge, perceptions, and feedback on the guidebook. The results of the study showed that participants’ awareness increased from 18% to 100% regarding understanding of mosquito characteristics, mosquito habitat reproduction, and how to monitor mosquito larvae. A total of 95% of students found the book very helpful, and 53 students requested digital access. Feedback highlighted the need for better visualization, accessibility, and more comprehensive content. In conclusion, the dissemination of the Jumantik guidebook was effective in improving health literacy among adolescents and strengthening their role as agents of change in dengue prevention.